In VitroStudies of Controlled Release Alfuzosin Matrix TabletsPrepared with Ethylcellulose and Hydroxypropyl Methylcellulose: Controlled release alfuzosin matrix tablets - Monzurul Amin Roni; Golam Kibria; Reza-ul Jalil (Iranian Journal of Pharmaceutical Sciences, 2009)
Extended release formulation of alfuzosin, an α-antagonist used for prostatic hypertrophy, is available in market. It is convenient for older patients to take only one tablet a day. Marketed alfuzosin formulation is three layered geomatrix tablet that requires special facilities, high cost, more time and complex operation than normal direct compression formulation. Therefore, a less complicated formulation is desired which can be prepared by conventional tools. The aim of the study was the development and in vitroevaluation of a controlled release dosage form of a freely soluble weakly basic drug (alfuzosin hydrochloride). Binary mixer of one hydrophilic polymer (hydroxypropyl methylcellulose) and one hydrophobic polymer (ethyl cellulose) was used in tablets prepared by direct compression, 32factorial design was chosen and the amount of two polymers were taken as independent variables.The percent drug released at 1, 6, 12, and 20 h were selected as response. The main effect and interaction terms were quantitatively evaluated using mathematical model. Dissolution data were fitted to zero order, first order, and Higuchi’s releasekinetics to evaluate kinetic data. According to Korsmeyer’s equation drug release followed both diffusion and erosion mechanism in all cases. Drug release was different from three fillers (microcrystalline cellulose, lactose and dibasic calcium phosphate).